Syzygium cumini(L.), Skeels fruit extracts: In vitro and in vivo anti-inflammatory properties. (10th May 2021) - Qamar, Muhammad; Akhtar, Saeed; Ismail, Tariq; Yuan, Ye; Ahmad, Naveed; Tawab, Abdul; Ismail, Amir; Barnard, Ross T.; Cooper, Matthew A.; Blaskovich, Mark A.T.; Ziora, Zyta M.
Abstract: Ethnopharmacological relevance: Syzygium cumini (L.) Skeels is an important medicinal plant utilized in the health care systems of Pakistan, India, Sri Lanka, and Bangladesh. S. cumini have been used to treat renal issues, indigestion, diabetes, dysentery, and employed in folk medicine to treat inflammations. It is known to anticipate antioxidant, anti-inflammatory, anticancer, anti-diabetic, anti-bacterial, antifungal, activities, and radioprotective activities. Material and methods: We examined the in vitro anti-inflammatory activities of S. cumini fruit extracts, evaluated using membrane stabilization, egg albumin denaturation, and bovine serum albumin denaturation assays. In vivo anti-inflammatory activity was also assessed, using murine models of carrageenan, formaldehyde, and PGE2 induced paw edema. Fractionation of active extracts was performed using HPLC, followed by LC-ESI-MS/MS analysis to identify the bioactive compounds responsible for anti-inflammatory activity. Results: The crude methanolic extract showed stronger in vitro and in vivo anti-inflammatory activities compared to other extracts. The most potent effects were observed in the formaldehyde induced paw edema assay wherein methanolic extract and standard indomethacin induced 72% and 88% inhibition against paw edema volume in comparison to control (normal saline) respectively. In the bovine serum albumin denaturation assay the methanolic extract induced 82% inhibition against denaturation as compared to control (phosphate buffer) while standard diclofenac sodium induced 98% inhibition. In contrast, 50% v/v MeOH:H2 O or 100% dichloromethane extracts displayed moderate to weak effects in the anti-inflammatory models. HPLC fractionation provided 6 active sub-fractions, four (MF2, MF3, MF6, MF7) from the 100% methanolic extract and two (HAF1, HAF3) from the 50% methanolic extract. The MF2, MF7, and HAF1 sub-fractions displayed potent activity in all studied in vitro assays. LC-ESI-MS-MS analysis tentatively identified delphinidin 3-glucoside, peonidin-3, 5-diglucoside, gallic acid, liquitrigenin, scopoletin, umbelliferon, and rosmanol from the 100% methanolic fractions. Myricetin, catechin, quinic acid, chlorogenic acid, ellagic acid, gallic acid, and caffeic acid were identified in the 50% methanolic fractions. Conclusions: These results demonstrate that S. cumini fruit extracts are a rich source of bioactive compounds that are worthy of further investigation as leads for anti-inflammatory drug discovery. Graphical abstract: Image 1